Potências do olhar em cena : montagem e sensorialidade no cinema - Oliveira, Germano Teixeira de (2016)
The goal of this research is to understand the potentialities involved in the shots of looks given by characters in films, trying to comprehend them under the light of the analysis of its presentification – a concept taken from the studies of the German theorist Hans Ulrich Gumbrecht. The act of looking will be analyzed in its potentiality of articulating the categories of time and space, by the editing process, on selected sequences of films produced between the years 1994 and 2016 that exemplify some of the constructions of these categories on the scene. This selection is given by a natural consequence of a higher amount of sensorial tendencies, which show up in cinema after the ending of mannerism as a predominant mise en scène, in the late 80s.